Comparative study of post-partum intra uterine contraceptive device insertion and interval intra uterine contraceptive device insertion in a tertiary care hospital - R., Manimegalai; R., Suganthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: NFHS (National Family Health Survey) 2005-2006 in India revealed that the contraceptive prevalence rate is 53.5%. 10% of all pregnancies are mistimed and 11% of all pregnancies are unwanted in India. Objective of present study was to compare the benefits and complications of postpartum IUCD insertion (PPIUCD) over interval IUCD insertion in a tertiary care hospital. Methods: It is a retrospective study conducted in the Department of Obstetrics and Gynecology, Govt. Mohan Kumaramangalam Medical College, Salem from 2009-2014. The cases of interval IUCD for the year 2009-2014 and PPIUCD cases for the year 2012-2014 both vaginal insertion and intracaesarean insertion were taken for study. Complications, benefits and reasons for removal were compared between the two groups. Results: The total number of cases of IUCD insertion significantly increased after the introduction of PPIUCD programme in 2012. The acceptance of IUCD insertion was steadily increasing after the introduction of PPIUCD even though the follow up of PPIUCD cases was less (32%). The rate of removal in patients who came for follow up was less in PPIUCD group (18%) compared to interval IUCD cases (57%) when the reason was menorrhagia. The most common reason for removal was menorrhagia in interval IUCD patients. Abdominal pain was the most common reason for removal in PPIUCD patients. The rate of expulsion was higher in PPIUCD (6%) compared to interval IUCD patients (<1%). No cases of perforation and no cases of pregnancy in situ were reported in PPIUCD cases during the study period. Even though the rate of infection and missing strings were higher in PPIUCD patients when compared to interval IUCD patients who came for follow up the number of women with infection in PPIUCD patients is less and easily managed with appropriate antibiotics. Conclusions: In India PPIUCD insertion soon after delivery is a safe, effective, reversible and reliable method of long term contraception. Both vaginal and intracaesarean insertions are safe, efficacious and convenient even though there are few complications which are easily manageable. There are no incidences of perforations, pregnancy in situ, ectopic pregnancy and low rates of infection. Hence PPIUCD is a promising approach to decrease the fertility rate in the field of family planning.